Implementation of the Digital Village Program by the Sumber Agung Village Government in Rimbo Ilir Sub-District, Tebo Regency - Dedi Epriadi; Miranti; Gesit Amanda (Jurnal Ragam Pengabdian, 2026)
The Digital Village Program is an initiative designed to harness village potential through the utilization of information and communication technology (ICT). This program aims to enhance the quality of public services, transparency, and community participation at the village level. This study analyzes the implementation of the Digital Village Program, the challenges faced, and its impacts on the welfare of the Sumber Agung Village community.This research adopts a qualitative approach, with data gathered through interviews, observations, and document analysis. Findings from the village government documents reveal that the Digital Village Program has improved administrative efficiency, expedited information access, and created new economic opportunities for residents of Sumber Agung Village, Rimbo Ilir Sub-District